Molecular Hydrogen Modulates T Cell Differentiation and Enhances Neuro-Regeneration in a Vascular Dementia Mouse Model - Dain Lee; Hyunjun Jo; Jong-Il Choi (Antioxidants)
This study explores whether molecular hydrogen (H2) administration can alleviate cognitive and immunological disturbances in a mouse model of vascular dementia (VaD). Adult male C57BL/6 mice underwent bilateral common carotid artery stenosis to induce VaD and were subsequently assigned to three groups: VaD, VaD with hydrogen-rich water treatment (VaD + H2), and Sham controls. Behavioral assessments using open field and novel object recognition tests revealed that VaD mice exhibited anxiety-deficient behavior and memory impairment, both of which were reversed by H2 treatment. Histological examinations showed pyknotic neuronal morphologies and elevated reactive oxygen species (ROS) in the VaD hippocampus, whereas H2 administration mitigated these alterations. Furthermore, VaD-induced downregulation of BCL2 was reversed in the VaD + H2 group, in parallel with increased IL-4 expression. Flow cytometric analyses revealed that VaD disrupted T regulatory cell homeostasis by significantly increasing their proportion, an effect reversed by H2 treatment, thereby restoring immunological balance. Transcriptomic evaluations confirmed that VaD suppressed key neuroprotective and anti-inflammatory genes, while H2 treatment restored or enhanced their expression. Collectively, these findings highlight the neuroprotective and immuno-modulatory potential of molecular hydrogen, suggesting that H2 supplementation may promote neuronal resilience, modulate T cell differentiation, and support cognitive recovery in vascular dementia.